Relationship between a sitting position and complaints of nonspecific low back pain among the Buton Sorong weavers - Zainul Muhlisi Mahfud Zulima; Anak Agung Gede Eka Septian Utama; Putu Ayu Sita Saraswati; Ni Luh Nopi Andayani (Physical Therapy Journal of Indonesia, 2023)
Background: Weaving has risk for experiencing nonspecific low back pain (LBP) that caused by bad posture and prolonged sitting duration. Poor sitting position causes musculoskeletal disorders, one of which is pain. Complaints of pain that is felt in the waist, causing functional limitation of movement when moving due to postural errors, are called nonspecific LBP. Weavers with good body positions have a low risk of nonspecific LBP complaints and increased productivity. This study aimed to determine the relationship between sitting position and nonspecific LBP complaints in Buton Sarong weavers in Baubau City. Methods: This study used an analytic observational research design with a cross-sectional approach. The research subjects were taken using probability and purposive sampling techniques. The independent variable measured was the sitting position using the rapid entire body assessment (REBA). The dependent variable measured was nonspecific LBP using a physiotherapy history-taking process. Results: There were 63 weavers in this study, 51 people (81%) had a low sitting position, and 12 (19%) had medium risk. The Spearman's rho non-parametric analysis test showed no relationship between sitting position and nonspecific LBP complaints in this population (p=0.819). Conclusion: There is no significant relationship between sitting position and nonspecific LBP complaints.